The mistress [compact disc, unabridged] - Steel, Danielle (Brilliance Audio, 2016)
Natasha Leonova's beauty saved her life. Discovered on a freezing Moscow street by a Russian billionaire, she has lived for seven years under his protection, immersed in rarefied luxury, while he pursues his activities in a dark world that she guesses at but never sees. Her home is the world, often on one of Vladimir Stanislas's spectacular yachts manned by scores of heavily armed crew members. Natasha's job is to keep Vladimir happy, ask no questions, and be discreet. She knows her place, and the rules. She feels fortunate to be spoiled and protected, and is careful not to dwell on Vladimir's ruthlessness or the deadly circles he moves in. She experiences only his kindness and generosity and believes he will always keep her safe. She is unfailingly loyal to him in exchange.